Increasing The Availability Of Post-Mortem Imaging Facilities Should Be Recommended For The Benefit Of The Ummah - Razrim Rahim; Nurul Kharmila Abdullah; Mohd Faisal Mohamed (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.